Positive Resources of School Class Communities—Determinants of Student Satisfaction - Tonči Bavčević; Boris Milavić; Damir Bavčević; Matej Babić; Dražen Čular (Education Sciences)
The aim of this study was to determine the factors affecting students’ satisfaction with their class community by measuring the contributions of “positive” resources: either the socio-demographic and individual characteristics of students, or common characteristics of the class community. The research was conducted anonymously using multiple questionnaires on a sample of 267 students attending the higher grades (5th–8th grades) of primary schools from an urban area of the city of Split. It was determined that social cohesion and prosocial behaviour within the class community were the strongest determinants and were also the most important positive resources of satisfaction with the class community. Individual psychological characteristics (especially self-esteem and hope) and the socio-demographic characteristics of students also played a significant role in explaining satisfaction with the class community, but their relative contribution was much weaker than social relations within the class community. The three types of psychological characteristics of the students were positively related to the degree of satisfaction with the class community, but this association was at a low level. More than half of the students were not completely satisfied with their class community. Furthermore, based on the five fundamental dimensions of intrinsic (IM) and extrinsic motivation (EM) within PE motivation, four types of students with different motivational characteristics were determined: the very low type; moderate type; very high IM and low EM type; and extremely high type. It is recommended that experts continue researching the relationship between psychological and social variables in class communities, as well as investigating the effectiveness of possible interventions aimed at the development and improvement of social relationships in the educational and sports talent development environment.